When the Subaltern Took the Postcolonial Turn - Roosa, John (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2006)
AbstractThis essay evaluates the changing research agendas of Subaltern Studies, an influential series of books on South Asian history that began in 1982. The essay criticizes the original research agenda as articulated by the series editor, Ranajit Guha, and the subsequent agenda proposed by several members of the Subaltern Studies collective. Guha initially proposed that studies of colonial India understand power in terms of unmediated relationships between “the elite” and “the subaltern” and endeavour to answer a counterfactual question on why the “Indian elite” did not come to represent the nation. The subsequent agenda first formulated in the late 1980s, while jettisoning Guha’s strict binaries and crude populism, has not led to any new insights into South Asian history. The turn towards the issues of modernity and postcolonialism has resulted in much commentary on what is already known. Some members of the collective, in the name of uncovering a distinctly “Indian modernity” and moving beyond Western categories, have reified the concept of modernity and restaged tired old debates within Western social theory.